Clinical pharmacist perspectives for optimizing pharmacotherapy within Enhanced Recovery After Surgery (ERAS®) programs. (March 2019) - Lovely, Jenna K.; Hyland, Sara Jordan; Smith, April N.; Nelson, Gregg; Ljungqvist, Olle; Parrish, Richard H.
Abstract: One of the most durable approaches to perioperative enhanced recovery programming has culminated in the formation of perioperative organizations devoted to improvements in the quality of the surgical patient experience, such as the Enhanced Recovery After Surgery (ERAS ® ) Society. Members of the American College of Clinical Pharmacy (ACCP) Perioperative Care Practice and Research Network (PRN) and officials from the ERAS ® Society present an opinion that: (1) identifies therapeutic options within each pharmacotherapy-intensive area of ERAS ® ; (2) generates applied research questions that would allow for comparative analyses of pharmacotherapy options within ERAS ® programs; (3) proposes collaborative practice opportunities between key stakeholders in the surgical journey and clinical pharmacists to manage drug therapy problems and research questions; and (4) highlights examples of pharmacist-led cost savings attributed to ERAS ® implementation. Clinical pharmacists, working in this manner with the perioperative team across the care continuum, have optimized pharmacotherapy towards measurable outcomes improvements, and stand ready to partner with inter-professional stakeholders and organizations to advance the care of our mutual patients. Highlights: Identifies pharmacotherapy-intensive areas of ERAS ® . Generates applied research questions for comparative pharmacotherapy analyses. Proposes collaborative practices between surgeons and clinical pharmacists. Highlights examples of pharmacist-led cost savings within ERAS ® implementations.